Wireless Powered NOMA Assisted Full-Duplex Cooperative U2U Communications System With Fluctuating Two-Ray Channel - Rahul Bajpai; Afraj Shabbir Shaikh; Naveen Gupta (IEEE Access)
Unmanned aerial vehicles (UAVs) are used for search and rescue, transportation, easy relocation, and stability. UAVs can also be utilized as aerial base stations to enhance the coverage for ground cellular users. This paper proposes non-orthogonal multiple access (NOMA) assisted full-duplex (FD) cooperative UAV-to-UAV (U2U) communications system wherein the UAV transmitter acts as an FD relay for cellular downlink signal. In addition, the UAVs employ an energy harvesting framework consisting of simultaneous wireless information and power transfer (SWIPT) and wireless power transfer (WPT) protocols to improve energy efficiency. The links between the communicating nodes are modeled by the fluctuating two-ray (FTR) fading, and a probabilistic mathematical model is developed for end-to-end cellular and U2U links. The closed-form outage expressions for U2U and cellular links are derived by performing an asymptotic analysis over a high transmit signal-to-noise ratio (SNR) regime. The impact of transmit-SNR, NOMA power allocation factor, and power splitting factor on the outage performance of the cellular and U2U links are analyzed. Results show that the cellular outage probability for a high SNR regime is independent of the FTR parameter, whereas U2U outage probability decreases monotonically and converges to zero.